Green Nanotechnology for Environmental Sensing and Monitoring - Anjum, Muhammad Shahbaz; Khan, Ismat Ullah (New Environmentally-Friendly Materials, 2023)
Environmental degradation driven by industrialization, urban expansion, and agricultural intensification demands advanced, sustainable monitoring tools capable of detecting contaminants at trace levels. Green nanotechnology—rooted in the principles of green chemistry—offers a pathway to develop high-performance environmental sensing systems while minimizing ecological and human health risks. This review examines the principles of green nanotechnology, emphasizing eco-friendly synthesis routes, life cycle considerations, and their influence on nanomaterial properties relevant to sensing. It scans the principal categories of nanomaterials (grassroots) synthesized with green methods, which include metal, metal oxide, carbon-based, and polymer frameworks, and their incorporation into optical, electrochemical, and mass-based sensitive systems. Examples of applications include water, air, soil, and climate-related monitoring, as well as technical, environmental, economic, and policy issues shaping their future adoption. New technologies emerging on the horizon include hybrid nanomaterials, biodegradable platforms, and AI-augmented data analysis, indicating the age of new sustainable monitoring systems. Green nanotechnology can therefore be termed an intersection between technological innovation and environmental care, involving real-time sensing with complete environmental conservation.